Optimal Risk-Sharing in Mortgage Contracts: The Effects of Potential Prepayment and Default - Jan K. Brueckner; Kangoh Lee (Center for Economic Studies and ifo Institute (CESifo), 2014)
Much of the literature on the economics of mortgage markets has studied the FRM-ARM choice made by individual borrowers. However, to decide if the outcome of such a choice is efficient or approximately so, it is necessary to explore the question of optimal risk-sharing in mortgage contracts. But since only a small literature has studied this question, more research is clearly warranted. The present paper helps fill this gap by developing a simplified version of Arvan and Brueckner's (1986a) model, using it to characterize optimal contracts in the absence of mortgage termination, and then exploring how termination via prepayment or default affects optimal risk-sharing. The broad conclusion of the analysis is that potential mortgage termination makes higher risk exposure for borrowers optimal.
Keywords: A00; 330; mortgage; risk-sharing; default; prepayment